Une autre histoire Histoire, temps et passé dans les Vies et Passions latines (IVe-XIe siècle) - Isaïa, Marie-Céline (Bibliothèque d'Histoire des Textes, 2023)
When writers document the life of a saint, they describe past events, they put them into a narrative context that serves to further their story and, at the same time, fit within a larger plan of salvation. Hagiography is therefore a form of historical writing, but it differs from that of chroniclers. The hagiographers of Late Antiquity sought to distinguish themselves from secular historians. However, their successors in the early Middle Ages were concerned with chronology and source comparison, leading to the development of scholarly techniques and ethical practices that closely align with those expected of historians. Consequently, their works shed new light on what the Middle Ages defined as history, while also revealing the historical culture and the way the Latin West shaped its understanding of the past through stories about saints.